Understanding the Role of Knowledge and Compliance in Iron Supplement Intake Among Anemic Adolescent Girls: A Cross-Sectional Study - Angelina, Saputri Lita; BD, Faridah; Fitriah, Iin Prima; Bebasari, Mardiani (RRZ Scientific Publishing, 2025)
Anemia remains a critical public health issue among adolescent girls in Indonesia, particularly in semi-urban areas where data are limited. This cross-sectional study examined the association between knowledge, compliance with iron supplementation, and anemia prevalence among 60 menstruating adolescent girls aged 12–18 years in Kurao Pagang, Padang City, from August to September 2024. Data were collected via structured questionnaires assessing knowledge and compliance, alongside hemoglobin measurements to determine anemia status. Results showed that 63% of participants had high knowledge, and 68% reported compliance with supplementation, yet 25% were anemic. Anemia prevalence was significantly lower in girls with high knowledge (15.7%) compared to those with low knowledge (40.9%), with high knowledge reducing anemia risk (OR = 0.26, 95% CI: 0.08–0.84, p = 0.024). Compliance was even more strongly associated with reduced anemia prevalence (14.6% vs. 47.4%; OR = 0.12, 95% CI: 0.04–0.37, p < 0.001). Despite these associations, anemia persists, indicating additional factors such as diet and socioeconomic status contribute to its prevalence. Integrated educational and supplementation interventions are vital to effectively reduce anemia among adolescent girls in similar semi-urban settings.